Proses pembekuan dan pengujian histamin ikan tuna (Thunus sp.) di PT. X, Banyuwangi - Siluh Putu Utari (Jurnal Perikanan dan Kelautan, 2023)
Histamine is an indicator of quality and food safety in fishery industry products, especially tuna derivative products. Histamine levels are an indicator of quality in tuna food products because if the histamine levels are high it will cause poisoning effects for humans who consume them. The aim of this research is to identify the process flow of freezing tuna (Thunus sp.) at PT. Independent Indonesian Tuna. As well as identifying the histamine content in raw materials and final products produced. This research was carried out in October December 2022 at PT. Independent Indonesian Tuna. Histamine testing method using biofish. The analysis of the data obtained will be analyzed descriptively. The process flow for freezing tuna fish has several stages including receiving, thawing, butchering, cooking, cooling, pre-cleaning (skinning), cleaning, inspect, metal detector I, packing I, metal detector II, Air Blast Freezer (ABF), packing II and cold storage. The results of histamine testing using the biophysical method on five raw materials with codes A, B, C, D, and E are 0; 2; 3; 4,2 ; 4 ppm. The test results for the five final product samples with codes A, B, C, D, E are 6.5 ; 3.2 ; 10.8 ; 7.6 and 5.3 ppm. The raw material temperature for tuna loin is around -10.4°C – (-9.1) °C. The histamine content of the test results in both raw material and final frozen tuna fish products is still below the standards set by the Company and SNI (100 ppm). Keywords: biofish, histamine, freezing, raw materials, tuna